Реакция упругой системы консоль – стержень на действие квазистатической и ударно-волновой нагрузок - Аникьев, И.И.; Максимюк, В.А.; Михайлова, М.И.; Сущенко, Е.А. (Прикладная механика, 2014)
A process of deformation of elastic system “console – rod” is experimentally studied under action of a shock wave on a surface of console and under quasi-static loading the console. Registration of quasi-static and non-stationary strains is carried out by PC with use of the high-precision portative eight-canal apparatus LMS SCADAS Mobile (Belgium). It is revealed that in the case of theoretical analysis of analogous problems the nonlinear statement is necessary.